Identification of Symbols in Indonesian Traditional Fairy Tales as a Health Promotion for the Prevention of Non-Communicable Diseases Diabetes Mellitus and Hypertension - Purnamayanti, Chelomitha Malindra; Ramadhania, Farhaiza; Siahaan, Rahelia Demak; Pertiwi, Rina; Yulianti, Yunika Tri; Sebayang, Susy Katikana (Universitas Airlangga, 2024)
Background: Non-communicable diseases are one of the groups of diseases with the highest causes of death in the world. This was shown by data from WHO that in 2023, around 74 percent of the causes of death in the world are non-communicable diseases that kill 41 million people per year. This is due to the lack of public understanding of the influence of risk factors for non-communicable diseases on the incidence of non-communicable diseases and complications that can be caused by non-communicable diseases. Therefore, the use of traditional Indonesian fairy tale symbols in health promotion media to prevent non-communicable diseases can be used as an alternative solution to overcoming this challenge. Aims: This study aims to identify, examine, and synthesize symbols in traditional Indonesian fairy tales that have the potential to they can be developed to improve health messages to prevent noncommunicable diseases, especially diabetes mellitus and hypertension. Method: The method used in this study was a Literature Review with a narrative review study design. The steps taken are to gather all the fairy tales with inclusion criteria are fairy tales that have symbols about non-communicable diseases and exclusion criteria are incomplete fairy tales, and then do the screening, identifying symbols, analyzing symbols, and selecting potential symbols. Results: Of the 21 relevant titles of Indonesian traditional fairy tales and legends, 85 symbols were identified. From the analysis of the meaning of each symbol, 16 symbols were found that have the potential to be used as promotions for the prevention of non-communicable diseases, diabetes mellitus, and hypertension, with 10 different symbol categories spread across 7 provinces in Indonesia. Conclusion: There are many symbols from traditional Indonesian fairy tales that have the potential to they can be used to increase the effectiveness of delivering health messages as an effort to promote the prevention of non-communicable diseases diabetes mellitus and hypertension. These symbols can be made into health messages nationally and can be flexibly used to create health messages in each region.